Economic prospects of pomegranate growing in the Spanish Mediterranean region - De Miguel M.D.; Melián A.; Fernández-Zamudio M.A. (II International Symposium on the Pomegranate, 2012)
The objective of this paper is to analyze origin price trends, as well as to determine the profitability of Spanish pomegranate farms through the evaluation of investments. This analysis is performed in parallel with mandarin, since citrus is one of the main tree crops with which it competes and shares territory. Although farmers in the Spanish Mediterranean have preferred to choose citrus in recent decades,its drop in value is encouraging the choice of alternative tree crops, and there will be areas, like the one studied here, where the interest in species with more favorable prospects, such as the pomegranate, will increase. This is possible if demand grows, supported by the notion that it is a healthy or functional food.
2. International Symposium on the Pomegranate, 2011/10/19-21, Madrid (Spain)